Post-coronavirus, how can we achieve food justice? - Wild, Sarah; Swinnen, Johan (European Commission, 2020)
The coronavirus pandemic disrupted the global food system and emphasised its structural inequity – from unequal food distribution to workers in the system going hungry. Experts are calling for a reimagining of the way we produce and distribute food so that everyone can access quality food. Despite producing more food by volume than humanity has to date, millions of people remain food insecure. Agriculture is also a major contributor to environmental degradation and climate change.